Annealing time dependence of the physical, electrical and pH response characteristics of spin coated TiO2 thin films. Issue 1 (November 2015) - Zulkefle, M A; Rahman, R A; Yusoff, K A; Abdullah, W F H; Rusop, M; Herman, S H
Abstract: Titanium dioxide (TiO2 ) thin film was deposited on indium tin oxide (ITO) substrate and used as sensing membrane of EGFET pH sensor. The thin film was fabricated using sol- gel spin coating method. All samples were annealed at 400 °C but the annealing time was varied. This is done to study the effects of annealing time on physical and electrical properties of titanium dioxide thin film. The sensitivity of each sample towards H + ion was measured and result shows that sample annealed for 45 minutes has the highest sensitivity (52.6 mV/pH). It is found that increasing annealing duration will increase the pH sensitivity but a limit will be reached at certain point. Longer annealing processes done beyond this point will results in lower pH sensitivity.